Faecal soiling: pathophysiology of postdefaecatory incontinence. (29th August 2013) - Pucciani, F.
Abstract: Aim: Passive postdefaecatory incontinence is poorly understood and yet is an important clinical problem. The aim of this study was to characterize the pathophysiology of postdefaecatory incontinence in patients affected by faecal soiling. Method: Seventy‐two patients (30 women, age range 49–79 years; 42 men, age range, 53–75 years) affected by faecal passive incontinence with faecal soiling were included in the study. Two patient groups were identified: Group 1 comprised 42 patients with postdefaecatory incontinence and Group 2 had 30 patients without incontinence after bowel movements. After a preliminary clinical evaluation, including the Faecal Incontinence Severity Index (FISI) score and the obstructed defaecation syndrome (ODS) score, all patients of Groups 1 and 2 were studied by means of endoanal ultrasound and anorectal manometry. The results were compared with those from 20 healthy control subjects. Results: A significantly higher ODS score was found in Group 1 ( P < 0.001). Endoanal ultrasound revealed a significantly diffuse thinning of the internal anal sphincter (IAS) in Group 2 ( P < 0.02) with a linear relationship between signs of IAS atrophy and the FISI score (ρs 0.78; P < 0.03). Anal resting pressure ( P max and P m ) was significantly lower in Group 2 ( P < 0.04). The straining test was considered positive in 30 (71.4%) patients in Group 1, significantly greater than in Group 2 ( P < 0.01). A significantly higher conscious rectal sensitivity threshold (CRST) was found in Group 1 patients ( P < 0.01). Conclusion: The ODS score, a positive straining test and high CRST values suggest that postdefaecatory incontinence is secondary to impaired defaecation.